PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KEPUASAN KERJA TERHADAP OCB PADA GURU SMA NEGERI 1 BLAHBATUH - Laksana, Alit Putra; Surya, Ida Bagus Ketut (E-Jurnal Manajemen, 2018)
The development of technology and science in this globalization era make education progress. Education plays an important role in creating quality and superior human beings. Teachers play an important role in the education system, especially in the school environment. This study aims to analyze the influence of transformational leadership and job satisfaction on organizational citizenship behavior (OCB). This research was conducted at SMAN 1 Blahbatuh. Sampling of this research using saturated sample method with 83 teachers of SMAN 1 Blahbatuh as respondents. Data were collected using interview method and questionnaire. Data analysis technique used in this research is multiple linear analysis. The results of this study show that transformational leadership has a positive and significant influence on OCB. Job satisfaction has a positive and significant influence on OCB.